ESTIMASI KARBON TERSIMPAN PADA NEKROMASSA TUMBUHAN DI RAWA LEBAK KECAMATAN MARTAPURA - Siam Melina (Bioscientiae, 2022)
South Kalimantan is one of carbon contributor with an area of swamp with ± 1,140,207 ha area of swamp land. The potential area for changed to be an agricultural land is ± 763,207 ha, and the remain used for pool when the rainy season is come. The highest C reserve is in biomass (mass of living-plant part) and necromass (mass of dead-plant part) at the top soil, microbe, and soil-organic matter. Based on description above, the problem is how much stored-carbon in necromass of plant at martapura lowland swamp, because the largest carbon storage found in necromass of plant. The purpose of this study was to estimate the stored carbon contained in necromass of vegetation in lowland swamp. This research has been done in Martapura from April to July 2009. Sampling is done at 4 location include Tungkaran village, Keramat Baru village, Sungai Rangas village and Sungai Tabuk village. Each sampling location divided into 2 stations in one sampling. Analysis of stored-carbon in necromass of plant is using Walkey and Black Method. The result showed that average ranges of carbon stored in plant necromass are 490,95 – 1744,66 gm-2.